Olympic rule 50: Bane toward human rights implications for the athletes - Chanda, Subhrajit; Sahoo, Sidheswar; Sahni, Shruti (Linguistics and Culture Review, 2021)
In the Tokyo Olympics, Raven Saunders, Bao Shanju and Zhong Tianshi were questioned by the IOC and got warnings due to their “performance of political demonstration” at the Olympic podium. We saw something similar during the 2012 London Olympic Summer Games when an indigenous boxer of Australia, Damien Hooper, was nearly disqualified from the Olympic competition for entering the ring wearing the Aboriginal flag shirt of Australia. The Olympics has had a history of maintaining a hypocritical form of political neutrality over the years. The Olympic Charter talks about sport being an essential medium in advancing the human rights of various individuals from different countries. However, it also chooses to stay neutral and gives preference to host nations. “Freedom of opinion and expression”, is a fundamental right enshrined in core international and regional human rights treaties and national laws. But it is also to be taken note that this freedom is restricted due to the “legitimate aims” of these treaties and laws. The Olympic Charter has followed suit and enacted a certain rule that prevents athletes from making demonstrations at the Olympic sites under the threat of disciplinary sanctions.